2017
DOI: 10.1111/cpr.12384
|View full text |Cite
|
Sign up to set email alerts
|

Loss‐of‐function of miR‐142 by hypermethylation promotes TGF‐β‐mediated tumour growth and metastasis in hepatocellular carcinoma

Abstract: These findings implicated that miR-142 was a tumour suppressor gene in HCC and often hyermethylated to increase TGF-β-induced development of hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…MiR-142-3p is a well-established tumor suppressive miRNA and has regulatory roles in multiple cell behaviors, such as migration and invasion. A recent study reported that miR-142 is hypermethylated in liver cancer [17]. Our study also observed the methylation of miR-142 in NSCLC cells.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…MiR-142-3p is a well-established tumor suppressive miRNA and has regulatory roles in multiple cell behaviors, such as migration and invasion. A recent study reported that miR-142 is hypermethylated in liver cancer [17]. Our study also observed the methylation of miR-142 in NSCLC cells.…”
Section: Discussionsupporting
confidence: 85%
“…It is commonly observed that tumor suppressive miRNAs are frequently methylated in cancers [15][16][17]. For instance, miR-145 is regulated by DNA methylation in prostate cancer [15].…”
Section: Discussionmentioning
confidence: 99%
“…The negative controls (NC) were scrambled oligonucleotides. Cell transfection was performed as described previously . Briefly, the miR‐552 mimics, inhibitors and NC purchased from RiboBio (Guangzhou, China) were transfected into cells at a concentration of 100 nmol/L via Lipofectamine 3000 (Invitrogen) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported that hypermethylation and/or demethylation of miRNA promoters can influence expression of EMT progression, such as for miR-211 [ 258 , 259 ] in melanoma cells, miR-129 [ 260 ] in HCC, miR-124 [ 261 ] in endometrial cancer, and miR-200 [ 262 ] and miR-203 [ 263 ] in distinct cell types. In some cases, epigenetic modulation of miRNA expression leads to up-regulation of TGF-β signaling such as for miR-142 [ 264 ] in HCC or to epigenetic modulators such as HDAC5 [ 265 ] in NSCLC. Alternatively, miRNAs can directly target epigenetic modulators such as DNMT1 by miR-152 [ 266 ] or lysine K demethylase 6B by miR-941 [ 267 ] leading to impaired EMT development, respectively.…”
Section: Contribution Of Micrornas To Epithelial-to-mesenchymal Trmentioning
confidence: 99%